Enhanced textile dye decolorization by marine-derived basidiomycete Peniophora sp. CBMAI 1063 using integrated statistical design - Bonugli-Santos, Rafaella C. (2016)
In the present study, the biotechnological potential of the marine-derived fungus Peniophora sp. CBMAI 1063 was investigated in relation to Reactive Black 5 (RB5) dye decolorization and degradation using an integrated statistical design composed of Plackett-Burman design (P&B), central composite design (CCD), and response surface methodology (RSM). RB5 dye was effectively decolorized (94 %) in saline conditions, without any detection of mutagenic compounds, and simultaneously, 57 % of total organic carbon (TOC) was removed in 7 days. The activity of lignin peroxidase (LiP) was not detected during the process. The gene expression of laccase (Lac) and manganese peroxidase (MnP) enzymes produced during the process was evaluated, and results from this experiment coupled with LC-MS analyses revealed that in the early stage of dye decolorization, a higher MnP gene expression and significant enzymatic activity was detected in Peniophora sp. CBMAI 1063 with the formation of p-Base and TAHNDS compounds. This paper reports innovative data related to the textile dye decolorization by the marine-derived basidiomycete Peniophora sp. CBMAI 1063, showing the metabolites formed and enzymatic action throughout the process in saline condition. The strategy used showed to be an efficient statistical approach that provides an attractive solution for the screening and simultaneous optimization of the degradation process.